Grade control geological mapping in underground gold vein operations - Dominy, Simon; Platten, I. (2012)
Grade control is a process of maximising value and reducing risk. It requires the delivery of tonnes at an optimum grade to the mill, via the accurate definition of ore and waste. It essentially comprises data collection, integration and interpretation, local resource estimation, stope design, supervision of mining and stockpile management. The foundation of all grade control programmes should be that of geological understanding led by clear and accurate mapping and representative sampling to drive appropriate estimation strategies and mining. Gold veins show features relating to erratic grade distribution (nugget effect), and variable geometry and internal architecture. These features include variations in dip, strike and width, late-stage faulting/shearing effects and vein continuity and type. Variations generally require close geological understanding to ensure optimum grade, minimal dilution and maximum mining recovery. A welldesigned grade control programme will prove to management and stakeholders that by applying geological knowledge, the mining process can be both efficient and cost effective. © 2012 Institute of Materials, Minerals and Mining and The AusIMM.